Constituições de sujeitos nas relações sociais de consumo : um estudo de peças publicitárias no setor bancário - Lima, Leonardo Vasconcelos Mattos (2007)
The increasing of influence power of the new capital apparatus as a life-style productors comes consecrating around the world as one of the historical phenomenons that, in some way, consolidates the marketing role in the constitution of desires and subjec